2016
DOI: 10.1007/978-1-4939-4011-0_18
|View full text |Cite|
|
Sign up to set email alerts
|

An Integrative Analysis of microRNA and mRNA Profiling in CML Stem Cells

Abstract: Integrative analysis of microRNA (miRNA) and messenger RNA (mRNA) in Chronic Myeloid leukemia (CML) stem cells is an important technique to study the involvement of miRNA and their targets in CML stem cells self-renewal, maintenance, and therapeutic resistance. Here, we describe a simplified integrative analysis using Ingenuity Pathway Analysis software after performing proper RNA extraction, miRNA and mRNA microarray and data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…More recently, a challenging hsa-mir183/EGR1/E2F1 axis has been reported to directly control CML stem cell behaviour 72. Most of these miRNAs have been extensively reviewed elsewhere 69,7377…”
Section: Cooperating Oncogenesmentioning
confidence: 99%
“…More recently, a challenging hsa-mir183/EGR1/E2F1 axis has been reported to directly control CML stem cell behaviour 72. Most of these miRNAs have been extensively reviewed elsewhere 69,7377…”
Section: Cooperating Oncogenesmentioning
confidence: 99%
“…By binding to the 3'-untranslated region (UTR) of target mRNA, miRNAs induce mRNA cleavage or translation inhibition (12). Each miRNA has multiple potential mRNA targets, and therefore, a broad-spectrum gene expression can be affected by an specific miRNA (13,14). Recent studies have demonstrated that miRNA inhibitory activity can be quantified by examining their target mRNA expression levels (15).…”
Section: Introductionmentioning
confidence: 99%